2021
DOI: 10.1186/s13765-021-00593-7
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous oxide emissions and maize yield as influenced by nitrogen fertilization and tillage operations in upland soil

Abstract: Previous studies simply focused on determining nitrous oxide (N2O) emissions from the soil under different tillage operations and nitrogen (N) fertilizations without considering crop yield. Therefore, the objective of this study was to determine the effects of different tillage operations and N fertilizations on N2O emissions and crop yield from upland soil. Two different tillage operations [conventional tillage (CT) and no-tillage (NT)] and N fertilizations [without urea (WOU) and with 186 kg N ha−1 of urea (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
2
5
0
Order By: Relevance
“…The lower average emissions suggest that basalt amendments decrease N 2 O emissions by increasing soil pH, and the lack of statistical significance could be due to another more dominant lever-in this case, soil moisture, as suggested by the machine learning framework. This implication that soil structure plays an important role in N 2 O fluxes agrees with observations suggesting that tilling practices strongly influence N 2 O fluxes (Mei et al, 2018;Kim et al, 2021;Jiang et al, 2022).…”
Section: Runsupporting
confidence: 90%
“…The lower average emissions suggest that basalt amendments decrease N 2 O emissions by increasing soil pH, and the lack of statistical significance could be due to another more dominant lever-in this case, soil moisture, as suggested by the machine learning framework. This implication that soil structure plays an important role in N 2 O fluxes agrees with observations suggesting that tilling practices strongly influence N 2 O fluxes (Mei et al, 2018;Kim et al, 2021;Jiang et al, 2022).…”
Section: Runsupporting
confidence: 90%
“…GC/MS conditions were maintained during the analysis, including a column temperature of 60 • C, heating temperature of 330 • C, and N 2 gas as a carrier [10,11]. For the calculation of gas flux, only 20 and 40 min gas sample concentrations were used because of asymptotic problems [10,29]. In addition, the linear interpolation between days was considered for the calculation of cumulative GHG emissions.…”
Section: Monitoring Greenhouse Gas Emissionsmentioning
confidence: 99%
“…Rainfall data during the experimental period indicated that heavy rainfall frequently occurred at the end of July and the beginning of September (Figure 2). Therefore, we could assume that increased WFPS in upland soil may have enhanced GHG emissions [11,29]. In addition, drying and rewetting cycle can cause the high peak of N 2 O and CO 2 in Figure 1.…”
Section: The Effect Of Amendments On Greenhouse Gas Emission Reductio...mentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of CO 2 is more complicated [33]. Kim [34] observed that the application of urea fertilizer in crop production increased cumulative N 2 O emissions, while conventional tillage also increased N 2 O relative to no-tillage.…”
Section: Introductionmentioning
confidence: 99%